Enhanced Asymptomatic Systemic Infection Caused by Plesiomonas shigelloides in a Captive Gray Wolf (Canis lupus) - Kyoo-Tae Kim (MDPI AG, 2021)
A 7-year-old male gray wolf was found dead at a zoo during exhibition. To determine the cause of death, histological and gross necropsy diagnoses and a molecular analysis were performed. The gross necropsy revealed a swollen abdomen, hemorrhagic exudates around the mouth, splenomegaly, a discolored liver, a congested kidney, hemorrhagic ascites, and dark gray-colored membranes and air bubbles in the fundus of the stomach. Rod-shaped bacteria were found in the liver parenchyma and hemorrhagic ascites using Giemsa staining. The nucleotide sequencing of the cultured bacteria identified the causative agent as Plesiomonas shigelloides, which is rarely responsible for systemic infections. This study describes a rare case and the first reported systemic gastrointestinal infection due to P. shigelloides in a zoo animal.